Pengaruh Influencer Credibility Terhadap Niat Pembelian Pada PenggunaTiktok Shop - Lukmanul Hakim; Hudyah Astuti Sudirman; Istimaroh . (CV. ITTC INDONESIA, 2025)
The low purchase intention among TikTok Shop users is a major issue, despite the platform’s considerable potential in the national e-commerce sector. This indicates a gap between market potential and actual purchase realization that has not been optimally utilized. As one of the most popular social commerce platforms, TikTok Shop offers interactive features such as live shopping and video reviews, which have the potential to increase online shopping activity. However, its purchase conversion rate still lags behind competitors like Shopee. Influencer credibility is believed to be an important factor because influencers can shape consumer perceptions through engaging, persuasive, and seemingly more trustworthy content. This study aims to analyze the influence of influencer credibility on the purchase intention of TikTok Shop users in Samarinda City. The research employed a quantitative approach with a survey method. A total of 127 active TikTok Shop users were selected as respondents. Data were collected through an online questionnaire and analyzed using simple linear regression, t-test, and the coefficient of determination (R²) to measure the influence of the independent variable on the dependent variable. The results indicate that influencer credibility has a positive and significant effect on purchase intention. The higher the level of trustworthiness, attractiveness, and expertise of an influencer, the greater the consumer’s tendency to purchase the promoted product. The R² value of 0.270 shows that 27% of the variation in purchase intention is explained by influencer credibility, while the remaining 73% is influenced by other factors not examined in this study.